Closure - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
JIFAM, Vol.3, Issue 1, March 2021 Framework for Facilities Management Services Procurement in Public Buildings in Abuja-Nigeria Sani Momoh, Jennifer Ayegba, Luqman Oyewobi, Calistus Ayegba, Abdulquadri Bilau & Richard Jimoh Hydropower Sustainability Assessment Protocol (HSAP) Implementation in Indonesia: A mini-review Novi Andriany Teguh & Ainul Firdatun Nisaa Weighting The Fire Protection Systems Technical Requirements to Determine Flats Reliability Against Fire Hazards Aris Aminulwahyu, I Putu Artama Wiguna & Tri Joko Wahyu Adi Purabaya Bus Station Service Performance in New Adaptation Period Putu Cinthya Pratiwi Kardita, Achmad Wicaksono & M. Ruslin Anwar Modeling and Optimization of the Compressive Strength of High Volume Fly Ash ECC with Low Modulus PVA Fiber Using Response Surface Methodology (RSM) Isyaka Abdulkadir & Bashar S. Mohammed Implementation of Risk Management in Property Projects I Wayan Muka & Agung Wibowo A New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in Indonesia Farrell Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert Wicaksono JIFAM, Vol.2, Supplement 1, December 2020 Life Cycle Cost Structure of a Government Office Green Building – Case of the Ministry of Public Works and Housing Main Building Domenico Adi Nugroho, Hitapriya Suprayitno, Tri Joko Wahyu Adi Effect of Waste Tire Rubber on the Durability Behavior of Cement Composites: A Review Isyaka Abdulkadir, Bashar S. Mohammed Preliminary Reflection on Basic Principle of Operation Management for Public Work Infrastructure Asset Management Ria Asih Soemitro, Hitapriya Suprayitno Comparing the Result of Infrastructure and Facility Demand Distribution Similarity Test Between Using Percentage Value and Real Value Hitapriya Suprayitno, Vita Ratnasari, Ria Asih Aryani Soemitro Learn Asset Management based on PTPN 9 Case – Preliminary Overview of the Institution, the Function, and the General Business Assets Soedarmawan Soewardi, Hitapriya Suprayitno, Ria Asih Aryani Soemitro